2022
DOI: 10.35848/1882-0786/acaaeb
|View full text |Cite
|
Sign up to set email alerts
|

A scheme to fabricate magnetic graphene-like cobalt nitride CoN4 monolayer proposed by first-principles calculations

Abstract: Based on the first-principles calculations, we propose a scheme to fabricate the cobalt nitride CoN4 monolayer, a magnetic graphene-like two-dimensional material, in which all Co and N atoms are in a plane. Under the pressure above 40 GPa, the bulk CoN4 is stabilized in a triclinic phase. With the pressure decreasing, the triclinic phase of CoN4 is transformed into an orthorhombic phase, and the latter is a layered compound with large interlayer spacing. At ambient condition, the weak interlayer couplings are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The structural and magnetic properties of these compounds were subsequently investigated. Additionally, Zhang et al have proposed a method for fabricating a magnetic graphene-like CoN4 monolayer through the use of first-principles calculations [53].…”
Section: Introductionmentioning
confidence: 99%
“…The structural and magnetic properties of these compounds were subsequently investigated. Additionally, Zhang et al have proposed a method for fabricating a magnetic graphene-like CoN4 monolayer through the use of first-principles calculations [53].…”
Section: Introductionmentioning
confidence: 99%
“…They investigated the structural and magnetic properties of 2D binary transition MN 4 . In another work, Shuo Zhang et al 56 also proposed a scheme for fabricating a magnetic graphene-like cobalt nitride (CoN 4 ) monolayer using firstprinciples calculations. Xiaoxu Sun et al 57 systematically analyzed the dual-site ORR mechanism on CoN 4 and CoN 2 embedded graphene.…”
Section: Introductionmentioning
confidence: 99%
“…They investigated the structural and magnetic properties of twodimensional binary transition MN4. In another study, Zhang et al proposed a scheme for fabricating a magnetic graphene-like cobalt nitride CoN4 monolayer using first-principles calculations [58]. Xiaoxu Sun et al [59] As theoretically reported, CoN4 may also have a diamond-like structure.…”
Section: Introductionmentioning
confidence: 99%